(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2022)
In this work, the effect of electromagnetic field on thermal performance of concentrated parabolic trough solar collector is studied experimentally. A two-axis tracking parabolic trough collector formed of a reflector (mirror tapes matrix), of (2m *1m), and an absorber copper tube (receiver) is designed. Water and water-based magnetic iron oxide (Fe3O4) nanofluid are used as heat transfer fluid in the collector. Three volume concentrations (0.3%, 0.5%, and 0.9%) of nanoparticles are investigated under a magnetic flux of (3.2, 4.3, 6.2, and 7.9*103 Gauss), which is installed at absorber inlet, middle, and exit. The three coils are connected to a DC-generator to control the electromagnetic field. The electromagnetic field effect on water flow in the absorber is found weak. A significant thermal improvement is figured when utilizing ferrofluid as a heat transfer fluid in the absorber. It is represented by higher temperature distributions in the absorber and higher solar collector efficiency compared with base fluid.